Mastery of Pillars of Prayer Among the Hearing-Impaired Students - Ainul Yaqin Abdullah; Manisah Mohd Ali (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
Hearing-impaired students must have the correct religious education and the same as typical pupils. Their inability factor can not be an excuse for leaving guidence and teaching in Islamic Education. This is because they need to live life as a muslim and be responsible as a servant of God. The purpose of this article is to discuss the mastery of pillar of prayer as well as issues and challenges in teaching and learning of Islamic Education among hearing-impaired students. This study is meta-analysis involving 25 articles. This article literacy search strategy use the two sources of electronic database, the Education Resources Information Center (ERIC) and EBSCOHOST, which is filtered based on the latest publications from 2010 to 2017. The first screening of 25 articles involves the curriculum, the practices of Islamic education and the practice of prayer among hearing-impaired students. The second filter using keyword mastery, issues and challenges of Islamic education among hearing-impaired students resulted in 12 article to be meta-analyzed. The first findings show that the mastery of prayer is at a weak level due to cognitive disability, weak language proficiency and the limitation of communication of hearing-impaired students to the study of religion. The second findings involve the aspects of skills among teachers, lack of terminology and sign language corresponding to religion and lack of teaching aids. The implications of this study are expected to open the eyes of all parties in order to improve the teaching and learning needs of Islamic education among hearing-impaired students.